Artificial Intelligence and International System Structure (2020)
Previous studies have investigated technology’s impact on international affairs, but few have analyzed the effect of artificial intelligence on the international system structure. This study integrates heterogeneous datasets and network science concepts with several power factors and artificial intelligence advances as a methodology to understand the evolution of the international system with a perspective around research, knowledge, innovation, and technology as an endogenous variable. Our findings indicate that the international fitness variable could be considered as a mechanism to interpret the system dynamics, especially when artificial intelligence interacts with different topics of the system. Overall, we provide quantitative evidence of the evolution of artificial intelligence innovations and technological power to identify system structure changes, both in central and peripheral countries.